Epidemiology and survival outcomes of patients with orbital region non-cutaneous squamous cell carcinoma: a population-based analysis - He, Lin-feng; Mou, Pei; Wei, Rui-li (Frontiers in Oncology, 2023)
Abstract Background: Non-cutaneous squamous cell carcinoma (ncSCC) of the orbital region is very rare. Thus, its epidemiological characteristics and prognosis are poorly understood. The aim of the study was to assess the epidemiological characteristics and survival outcomes of ncSCC of the orbital region. Methods: Incidence and demographic data on ncSCC of the orbital region recorded from 1975 to 2018 and 1975 to 2019, respectively, were extracted from the Surveillance, Epidemiology, and End Results (SEER) database and analyzed. The chi-square test was used to calculate the differences between groups. Univariate and multivariate Cox regression analyses were performed to determine the independent prognostic factors for disease-specific survival (DSS) and overall survival (OS). Results: The overall incidence of ncSCC of the orbital region from 1975 to 2019 was 0.68/1,000,000, and the incidence showed an increasing trend during this period. A total of 1265 patients with ncSCC of the orbital region (mean age, 65.3 years) were identified in the SEER database. Of these, 65.1% were aged ≥60 years, 87.4% were White, and 73.5% were male. The conjunctiva (74.5%) was the most common primary site, followed by the orbit (12.1%), lacrimal apparatus (10.8%), and overlapping lesion of the eye and adnexa (2.7%). Multivariate Cox regression analysis revealed that age, primary site, SEER summary stage, and surgery were independent prognostic factors for DSS, whereas age, sex, marital status, primary site, SEER summary stage, and surgery were independent prognostic factors for OS. Conclusions: The incidence of ncSCC of the orbital region has increased over the past 40 years. It usually affects White people, males, and people aged ≥60 years, and its most common site is the conjunctiva. Orbital SCC has worse survival outcomes than SCC of other sites in the orbital region. Surgery is the independently protective treatment for ncSCC of the orbital region.